Correction: Interprofessional collaboration during a specialised mobile palliative care service pilot in the rural area of Lucerne. - Sahra Maria Anna Bucher; Anne Marie Schumacher Dimech; Beat Müller; Patrick E Beeler (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0308256.].